Fungsi Komunikasi Kelompok dalam Progam Serap Gabah (Sergab) (Kasus pada Kelompok Tani Sri Rahayu Desa Purwosari, Kecamatan Babadan, Kabupaten Ponorogo, Jawa Timur) - ROSANA WIJAYANTI SETYANING; I DEWA PUTU OKA SUARDI; I GEDE SETIAWAN ADI PUTRA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
The Function of Group Communicationin the Unhulled Rice Grains Subsidiary Program / Serap Gabah (Sergab),(Case in Sri Rahayu Farmers Group of Purwosari Village,Babadan Sub-District, Ponorogo Regency) The Serap Gabah Program (Sergab) is a national program set up to tackle the fallingrice prices at the farmers' level at the time of harvest. The launching of the program is inline with the instruction of the President of Republic of Indonesia in cooperation withthe rural military officer / Babinsa, Extension Agent/PPL, and the Logistics Agency ofBulog. As a new program in agriculture, Sri Rahayu Farmers Group in PurwosariVillage, Babadan Sub-District, Ponorogo Regency is one of the farmer groups thatreceived the Sergab program. This study aims to determine the application of groupcommunication functions in Sergab program at Sri Rahayu Farmer Group of PurwosariVillage, Sub-District of Babadan, Ponorogo Regency. The sampling technique is usingsimple random sampling method. Data analysis method used is descriptive analysis.Based on the descriptive analysis of group communication function in the Serap Gabah(Sergab) program at Sri Rahayu Farmer Group of Purwosari Village, BabadanSubdistrict, Ponorogo Regency is categorized as good enough with achievement scoreof 3.21. The farmer members of Sri Rahayu Farmer Group should be more active intaking the agricultural extension program of Sergab, so that they gain insights from theinformation given by the extension agents of PPL, chairman of Sri Rahayu FarmerGroup is expected to actively encourage his members to follow Sergab program andAgricultural Extension as the activator of the Sergab program to further improvecommunication skills, especially persuasive communication, so that the persuasivecommunication function in the implementation of Sergab program can be wellorganized.